Sustainable Supply Chain Management: Supporting Sustainability in Consumer Goods Companies - Suwanda Suwanda (Jurnal Restorasi : Hukum dan Politik, 2023)
Sustainability is a key focus in modern business strategies, especially in the consumer goods sector which often faces pressure to reduce environmental impact and increase social responsibility. This research aims to identify and analyze sustainable supply chain management strategies in the context of the consumer goods industry. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of Sustainable Supply Chain Management (SSCM) in consumer goods companies has had a positive impact in creating a more sustainable supply chain. Selection of environmentally friendly raw materials, efficient production practices and close collaboration with sustainable suppliers are key aspects that improve a company's sustainability performance. Transparent reporting regarding environmental and social impacts also helps build stakeholder trust and improve the company's reputation. These results underscore that SSCM is not only an ethical principle, but also an effective strategy in meeting the demands of a market that increasingly values social and environmental responsibility.